Reactive oxygen species contribute to the release of volatile organic compounds from Chlamydomonas reinhardtii during programmed cell death. Issue 1 (5th November 2014) - Zuo, Zhaojiang; Chen, Zhengzhen; Shi, Menglin; Zhu, Yerong; Bai, Yanling; Wang, Yong
Summary Acetic acid at pH 5.0 can induce programmed cell death (PCD) in Chlamydomonas reinhardtii cells, and abundant volatile organic compounds (VOCs) were released during the process. In this study, the caspase‐3‐like activity was determined during the PCD, and it was increased significantly after 1 h. During the PCD, the dynamic release of VOCs from the cells was analyzed, and the emissions of total VOCs were raised markedly and reached the highest level at 2 h. Among the seven types of VOCs, such as alkanes, alkenes, terpenoids, alcohols, aldehydes, ketones and esters, three oxygenated compounds (aldehydes, ketones and esters) showed the most significant increase. O2‐· and H2O2 were rapidly accumulated to high levels in the cells at the beginning of the PCD, but their content was reduced during the process. The activities of antioxidant enzymes were reduced gradually and even disappeared completely, demonstrating that the reduction of reactive oxygen species (ROS) may not be scavenged by the antioxidant enzyme system. ROS have an intense oxidation and scavenging ability to volatile compounds, and the oxidation results in the production of oxygenated compounds. Therefore, the abundant production of oxygenated compounds indicated that ROS may play an important role in the dynamic release of VOCs from C. reinhardtii cells during PCD.